PEMBELAJARAN MODEL INQUIRI TERBIMBING PADA MATERI BESARAN DAN SATUAN UNTUK MENINGKATKAN KETERAMPILAN GENERIK SAINS DAN HASIL BELAJAR MAHASISWA - Mukhlis Mukhlis (UIN AR-RANIRY, 2017)
This study aims to determine the effect of guided inquiri learning model on the quantity and unit materials to improve the KGS and student learning outcomes. This research is a quasi-experimental type / model with pretest-posttest group design using the control class. Research samples were given treatment through the model in the experimental class. The data collection activities were conducted by comparing the final test results between the experimental and control classes for KGS mathematical modeling and student learning outcomes. Data processing is done by t-test for different test. This research was conducted on Chemistry Education Program FITK UIN Ar-Raniry. The results showed that there are differences in the ability of students 'mathematical model and students' learning outcomes with guided inquiry learning model. The mean value of KGS model of experimental mathematics class is 75,20 higher than control class that is 65,53. For the value of learning result obtained experimental class equal to 73,67, higher than control class equal to 67,72. Result of t-test result of learning result known from result t arithmetic = 1,70 with dk = 64 and t table 1.67, where t count> ttabel that is 1.70> 1.67. This shows that the Ho hypothesis is rejected and Ha accepted. So that learning with guided inquiry model has an effect on the ability of KGS mathematical modeling and student learning outcomes.